A Simple and Convenient Method for Synthesis of Artemisinin Dimer through Aliphatic Nitro Compounds - Srivastava, Nitin; Rathore, B.K.; Vishnoi, R.K.; Bajpai, Sangeeta (Asian Journal of Chemistry, 2020)
A simple way of synthesis of artemisinin dimer using nitro aliphatic compounds is reported. Herein, few artemisinin monomers and dimers have been synthesized with the help of linker nitroalkanes using iron catalyst supported on polymer (Fe/SBA-15). The synthesized artemisinin shows good anticancer and antimalarial activities.